Exponential sampled-data control for T–S fuzzy systems: application to Chua's circuit. Issue 16 (10th December 2019) - Gunasekaran, Nallappan; Saravanakumar, Ramasamy; Syed Ali, M.; Zhu, Quanxin
ABSTRACT: This study deals with the chaotic phenomenon of nonlinear Chua's circuit for power generator systems. Takagi–Sugeno (T–S) fuzzy model of a nonlinear system is established. By constructing a suitable Lyapunov functional, exponential stability conditions are obtained for fuzzy systems. Based on the sampled-data control theory, extreme sensitivity is visualised in the state trajectory depending on the initial conditions and sampled-data fuzzy controllers are designed in the form of linear matrix inequality (LMI). Finally, some numerical simulation results are shown that the sampled-data fuzzy control system adopts a well-designed methodology.